Water footprint characteristic of less developed water-rich regions: Case of Yunnan, China - Qian, Yiying; Dong, Huijuan; Geng, Yong; Zhong, Shaozhuo; Tian, Xu; Yu, Yanhong; Chen, Yihui; Moss, Dana Avery (Water research (Oxford), 2018)
Rapid industrialization and urbanization pose pressure on water resources in China. Virtual water trade proves to be an increasingly useful tool in water stress alleviation for water-scarce regions, while bringing opportunities and challenges for less developed water-rich regions. In this study, Yunnan, a typical province in southwest China, was selected as the case study area to explore its potential in socio-economic development in the context of water sustainability. Both input-output analysis and structural decomposition analysis on Yunnan's water footprint for the period of 2002–2012 were performed at not only an aggregated level but also a sectoral level. Results show that although the virtual water content of all economic sectors decreased due to technological progress, Yunnan's total water footprint still increased as a result of economic scale expansion. From the sectoral perspective, sectors with large water footprints include construction sector, agriculture sector, food manufacturing & processing sector, and service sector, while metal products sector and food manufacturing & processing sector were the major virtual water exporters, and textile & clothing sector and construction sector were the major importers. Based on local conditions, policy suggestions were proposed, including economic structure and efficiency optimization, technology promotion and appropriate virtual water trade scheme. This study provides valuable insights for regions facing “resource curse” by exploring potential socio-economic progress while ensuring water security. [Display omitted] •Both social and economic perspectives should be considered when ensuring local water security.•Water footprint of a less developed water-rich region is analyzed.•Input-output analysis and structural decomposition analysis are used.•Policy suggestions based on local realities are proposed.